Consumer’s Attitude and Willingness to Pay for Organic Rice - Qisthy Nur Fathia; Rita Nurmalina; Megawati Simanjuntak (School of Business, IPB University (SB-IPB), 2018)
Government’s support for Go Organic program provides a significant effect on the increasing organic land from only 71 thousand hectares in 2010 to 113 thousand hectares in 2014. This is caused by the shifting lifestyle of consumers who are more concerned about health. Rice as one of carbohydrate sources consumed by Indonesian people has an organic variant which is favored by many consumers. This study involved 100 households which were intentionally selected based on their convenience and readiness to be interviewed. This research was also conducted to analyze the comparison of consumer’s attitudes on organic and non-organic rice and to analyze consumer’s willingness to pay (WTP) for organic rice. Fishbein and Contingent Valuation Method were used as an analytical tool to find out the consumers’ attitudes and the maximum values that they are willing to pay. Consumers of non-organic rice had a more positive attitude on non-organic rice compared to organic rice with a WTP value of Rp 20,000 and the potential opportunity value that can be projected for organic rice in Bogor City is IDR291,788,621,400 per month.Keywords: consumer’s attitude, contingent valuation method, fishbein, organic rice, willingness to pay